The Impact of the Elastic Modulus of Shell Structures on the Stress Field in Concrete - Tang, Dongyang; Wang, Mingyuan; Bondarenko, S. N.; Rudnov, V. S. (БНТУ, 2025)
This study investigates the response ability of external additives in shell structures to matrix cracks. Starting with the analysis of the stress field around the carrier, we establish a strength model for shell structures. Based on an empirical formula for the elastic modulus fitted from experimental data, we analyze the stress coefficients of matrices with different elastic moduli for the shell additives. The findings reveal that an increase in the elastic modulus of the shell leads to a greater maximum stress concentration coefficient in the shell.